Perancangan Mesin Penggiling Jagung Menggunakan Metode Axiomatic House Of Quality (AHOQ) - Wesly Mailander Siagian; Amos Evander Tambunan (Program Studi Teknik Industri Universitas Setia Budi, 2024)
The high production yield in the agricultural sector is undoubtedly related to the processing of agricultural products. Currently, the community in Sinarsabungan Village still prefers selling whole corn instead of corn flour, including the Sinta Uli Farmers' Group. However, in general, corn flour is more expensive than whole corn because it is more nutritious and used for direct consumption or as a higher-quality raw material for animal feed. Therefore, a milling machine is needed to facilitate the farmer group members in corn milling. Subsequently, data collection in the form of the voice of the customer was conducted through observations, interviews, and questionnaire surveys. Through this research, a corn milling machine was designed using the Axiomatic House of Quality (AHOQ) method, which can be used by the farmer group as an appropriate technology in the agricultural sector. The design parameters were obtained from the AHOQ mapping, which included using sieves with fineness levels of 40 mesh, 80 mesh, and 100 mesh. The machine was driven by a 6.5 hp gasoline-powered engine with a shaft rotation of 3250 rpm and utilized a drive wheel. Subsequently, the design was created using Solidworks software. The resulting design was then developed into a product and subjected to testing. The results showed that the milling machine was capable of producing a milling capacity of up to 70,092 kg/hour, and the milling output met customer requirements. The equipment was constructed using iron material with a weight of 60 kg.